Ultrasensitive detection of DNA methyltransferase activity: a novel dual-amplification fluorescence technique. Issue 22 (5th October 2022) - Wen, Qilin; Li, Dandan; Huang, Guidan; Xi, Huai; Pan, Hongcheng; Zhang, Lianming; Li, Ziyuan; Xiao, Xiaofen; Zhu, Wenyuan
Abstract : A dual amplification fluorescence strategy was developed for the ultrasensitive detection of Dam MTase activity based on strand displacement amplification coupled with rolling circle amplification. Abstract : DNA methyltransferase (MTase) is an important regulatory enzyme in various biological processes. However, current methods for investigating MTase activity are still limited in terms of sensitivity and/or generality. Herein, we proposed a dual amplification fluorescence strategy for the ultrasensitive detection of DNA adenine methylation methyltransferase (Dam MTase) activity based on strand displacement amplification (SDA) coupled with rolling circle amplification (RCA). In this study, the hairpin probe could not be cleaved by Nt.AlwI nicking endonuclease (Nt.AlwI) in the presence of Dam MTase, and the subsequent SDA–RCA reaction was blocked, resulting in a weak fluorescence signal. Moreover, the blocking effect was more pronounced at a higher concentration of Dam MTase. This assay provides a very low detection limit (down to 0.0067 U ml −1 ), as well as good selectivity against other types of MTases ( e.g., CpG methyltransferase (M.SssI MTase)). In addition, the analytical mode improves the generality and can be extended to the detection of other types of DNA MTases.